Pengaruh pemberian pakan dengan presentase yang berbeda terhadap pertumbuhan ikan Patin (Pangasius pangasius) yang dipelihara di bak plastik - Mardani Mardani (Fakultas Peternakan Universitas Kristen Palangka Raya, 2017)
These experiments provide information on artificial feed, which is needed by fish in its growth. The goal is to determine the effect of artificial feeding with a different percentage of the growth of catfish (Pangasius pangasius) maintained in a plastic container. The best results in this experiment is the artificial feeding 7% of the protein content of 25-30%, fat 5-7%, carbohydrates 4-6%, and DE 2.600 to 2.800 Kcal / gram.